Offline or online?: EFL students’ perceptions on working in face-to-face and virtual learning modes - Yusny, Rahmat; Rizki, Fitria; Trisnawati, Ika Kana; Mulia, Mulia (Englisia Journal, 2021)
Given the intensified number of online learning activities and having inadequate knowledge to identify the details of how it was organized within increased students’ language learning ability; this study focused on identifying the students’ perceptions of learning in two different situations. This study investigated how students perceived working in a new learning mode (online learning activity) compared to the traditional or face-to-face learning mode (offline learning activity) in regards to the learning frameworks, including the depth and comprehensiveness of learning, appropriate length for learning, comfortability of learning, and flexibility of learning. Ten students were selected to be the participants of the current study; all of whom were sixth and eighth semester students at the Department of English Language Education of Universitas Islam Negeri Ar-Raniry Banda Aceh. They were served by several questions related to their experiences working on two different learning modes. The findings revealed that working in offline learning mode was still the common preference among the students and only a few of them preferred online learning. Even more interesting was the finding of one or two students who perceived no differences between participating in offline and online class learning activities. In addition, the findings also indicated that interaction between the course instructors and students still becomes a prominent element on the students’ satisfaction and comfort of learning. The students also suggested that the keys to their satisfactory learning experiences are access to learning materials and to their class instructors. To conclude, this study also provides new insights on what matters the most to the students’ learning experiences with respect to the current online learning trend.